Anforderungen an ein Next Generation LMS zur Unterstützung von Personalisierung aus bildungswissenschaftlicher Perspektive - Claudia de Witt; Heike Karolyi (FernUniversität Hagen, 2021)
The current generation of learning management systems (LMS) is essentially determined by a so-called transmission model of education, which has to be rethought in terms of lifelong learning due to the requirements of the digitalized society for the growing generation as well as for the adult generation. Technologies of AI and learning analytics enable the transition to concepts of hybrid course designs, to concepts of active learning and to new approaches of measuring individual study progress and designing personalized learning support. In three examples, this article explains how approaches to personalization are implemented in projects at the the Research Cluster D²L² "Digitalization, Diversity and Lifelong Learning. Consequences for Higher Education." of the FernUniverität in Hagen and refers to the implication for a next generation LMS that arise from educational perspectives.